4CPS-381 Proactive medication reconciliation and patient flow in the emergency department admissions. (14th March 2021) - Hanlon, C; Mccarthy, S; Lynch, D
Abstract : Background and importance: Pharmacist led medication reconciliations (MR) are the most exhaustive and accurate MRs. 1–4 Proactive MRs have shown several clinical and statistical benefits over retroactive MRs, particularly in improving patient flow. 5 Aim and objectives: To determine the feasibility of proactive pharmacist led MRs during emergency department (ED) admission and the patient flow impact. Material and methods: This was a mixed method feasibility study: quantitative prospective study of retroactive versus proactive MRs in the ED; qualitative semi-structured interviews with ED nurses and doctors and admitting doctors. Within the pre-determined feasibility domains of acceptability, demand, integration and practicality, major themes were determined as described in the results. Results: Acceptability: Qualitative: All interviewees thought pharmacists should lead MRs and considering the service had a positive impact on workflow. Quantitative: Pharmacists utilised a greater number of and more accurate medication information sources versus other healthcare professionals. Workflow improved, saving up to 19.5 min per proactive MR. Demand: Qualitative: Many thought we could reduce the amount of MRs completed and subsequently not admitted through targeting more complex patients. Improved prescribing and reducing late/missed doses were significant themes. Most used the service when available. Quantitative: The number of MRs completed increased from 5.2 to 8.6 per day. 20% of proactive MRs were subsequently not admitted. 80% of retroactive MRs detected an error. Time from presentation to MR completion was reduced from 20.5 to 2.5 hours. Integration: Qualitative: Staffing and costs were considered barriers to integration. Targeted approach, integrated into admissions and linking with the medication flow technician service was preferred. Face-to-face communication was preferred. Quantitative: Project saves were up to 19 077.18€/year (excluding error avoidance savings). Practicality: Qualitative: Most stakeholders were aware of the project despite difficulty spreading information. MR location/layout was suitable. Admitting doctors looked for MR information within the clinical notes and ED doctors within the ED notes. Conclusion and relevance: This study demonstrated that pharmacist led proactive MRs in the ED were feasible and cost effective. It should be integrated into admissions after triage, with the aim of targeting more complex patients. References and/or acknowledgements: Galvin, et al . Clinical pharmacist's contribution to medication-reconciliation on admission. Int J Clin Pharm 2013;35 :14. Grimes, et al . Relative accuracy and availability of an Irish National Database of dispensed medication. J Clin Pharm 2013;38 (3). Bell, et al . Association of ICU or hospital-admission with unintentional discontinuation of medications. JAMA 2011;306 :840–7. Grimes, et al . Collaborative pharmaceutical-care in an Irish hospital. BMJ 2014;25 :574–83. Renet, et al . Implementation of proactive medicines-reconciliation to reduce drug errors. EJHP 2015;22A168-A. Conflict of interest: No conflict of interest